PHYSICAL METHODS OF REHABILITATION IN CANCER PATIENTS AFTER COMBINED MODALITY TREATMENT FOR BREAST CANCER - V. E. Tishakova; E. V. Filonenko; V. I. Chissov; N. A. Efimenko; A. N. Urlova (Biomedical Photonics, 2017)
According to worldwide statistics breast cancer is the most common cancer in women. Despite the success in current methods of treatment post-operative period in major of patients is characterized by post-mastectomy syndrome which leads to impairment in daily activities, difficulties in social adaptation and consequently to dicrease of the quality of life. The specific causes, risk factors, characteristics of clinical and pathogenetic manifestations of post-mastectomy syndrome are described in detail in this review. Different approaches to post-mastectomy syndrome classification, its clinical and instrumental diagnosis are defined. Based on more than 40 publications of Russian and foreign authors, the issue of selection of appropriate treatment tactics for the syndrome is investigated and discussed in detail. A considerable part of the review is focused on the use of physical methods of treating the post-mastectomy syndrome. It is observed that an increasing number of specialists gives preference to methods of conservative treatment special of which are medical gymnastics, complex decongestive therapy and compression therapy. On the other hand, the absence of the unified treatment algorithms is challenging for clinicians. Therefore, its development with the focus on patient-specific approach is a crucial task for modern rehabilitology in breast cancer surgery.